Private Higher Education: Even France, Even For-Profit - Casta, Aurélien; Levy, Daniel (International Higher Education, 2016)
The dramatic growth of private higher education (PHE) in France, including a significant for-profit component, clashes with traditional notions of an omnipotent state ruling over higher education. But in fact the post-Napoleonic state has generally been accepting of the private educational sector, which has evolved from a religious to a markedly commercial orientation.